Evaluating the Response of Global Column Resistance to a Large Volcanic Eruption by an Aerosol-Coupled Chemistry Climate Model - Xie, Yushan; Zhang, Ruyi; Zhu, Zhipeng; Zhou, Limin (Frontiers in Earth Science, 2021)
Global electric circuits could be the key link between space weather and lower atmosphere climate. It has been suggested that the ultrafine erosol layer in the middle to upper stratosphere could greatly contribute to local column resistance and return current density. In previous work by Tinsley, Zhou, and Plemmons (Atmos. Res., 2006, 79 (3–4), 266–295), the artificial ultrafine layer was addressed and caused a significant symmetric effect on column resistance at high latitudes. In this work, we use an updated erosol coupled chemistry-climate model to establish a new global electric circuit model. The results show that the ultrafine aerosol layer exits the middle stratosphere, but due to the Brewer-Dobson circulation, there are significant seasonal variations in the ion loss due to variations in the ultrafine aerosol layer. In the winter hemisphere in the high latitude region, the column resistance will consequently be higher than that in the summer hemisphere. With an ultrafine aerosol layer in the decreasing phase of solar activity, the column resistance would be more sensitive to fluctuations in the low-energy electron precipitation (LEE) and middle-energy electron precipitation (MEE) particle fluxes.